Bioaccumulation of mercury and transcriptional responses in tusk (Brosme brosme), a deep-water fish from a Norwegian fjord. (September 2021) - Olsvik, Pål A.; Azad, Atabak M.; Yadetie, Fekadu
Abstract: High concentrations of mercury (Hg) have been documented in deep-water fish species from some Norwegian fjords. In this study, tusk ( Brosme brosme ) was sampled from four locations in the innermost parts of Sognefjorden in Western Norway. Total Hg and methylmercury (MeHg) levels were measured in liver tissue. To search for potential sublethal effects of Hg, we characterized the hepatic transcriptome in tusk with high and low levels of Hg bioaccumulation using global transcriptomics analysis (RNA-seq). The results showed that there was a significant correlation between fish weight and accumulated concentrations of MeHg but not total Hg. MeHg accounted for 30–40% of total Hg in liver of most of the fish, although at concentrations above 2–3 mg Hg/kg wet weight the percentage of MeHg dropped considerably. Transcriptome analysis resulted in hundreds of differentially expressed genes in the liver of tusk with high Hg levels. Functional enrichment analysis suggested that the top affected pathways are associated with protein folding, adipogenesis, notch signaling, and lipid metabolism (beta-oxidation and phospholipids). Based on transcriptional responses pointing to well-known effects of Hg compounds in fish, the study suggests that tusk in Sognefjorden could be negatively impacted by Hg bioaccumulation. Highlights: High levels of Hg in deep-water fish in inner parts of fjords. The MeHg/total Hg ratio drops in liver of tusk with high Hg levels. Many DEGs were differentially expressed in liver of tusk with high Hg levels. Top affected pathway was protein folding. Adipogenesis, notch signaling, and lipid metabolism pathways also affected.